Production of Graphene By Coconut Shell As an Electrode Primary Battery Cell - Elsa Pasaribu; Rikson Siburian; Minto Supeno (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2023)
Abstract: Coconut shells are a natural resource that contains a lot of carbon (C). The pyrolysis process can be used to create coconut shells. A single layer of carbon atoms that have undergone sp2 hybridization to form a hexagonal, two-dimensional structure is known as Graphene. Graphene has excellent potential for battery manufacturing applications, supercapacitors, etc. Activated carbon and the pyrolisis method of producing Graphene were combined and heated to 600 oC for one hour. The graphene generated is assessed using an XRD, SEM-EDX, TEM, Raman, and conductometer. The results of the X-ray diffractogram analysis revealed that the peaks at 2θ = 23,87o and 44,5o are not particularly sharp and slightly broadened. It means Graphene are well formed. SEM-EDX investigation reveals that the surface size and shape structure is smaller and thinner, a flat pile dominated by carbon atoms. The result of conductometer analysis shows the electrical conductivity of Graphene is quite good, but Graphene can still not control the movement of electrons. Graphene has layer distances between Graphene and Graphene layers are 3.3 Å (TEM data), with many Graphene layers being 0.85 (multi-layer) (Raman data).Abstrak: Batok kelapa merupakan salah satu sumber daya alam yang mengandung banyak karbon (C). Proses pirolisis dapat digunakan untuk membuat batok kelapa. Satu lapisan atom karbon yang telah mengalami hibridisasi sp2 untuk membentuk struktur dua dimensi heksagonal dikenal sebagai Grafena. Grafena memiliki potensi besar untuk aplikasi pembuatan baterai, superkapitasitor, dan sebagainya. Karbon aktif dengan metode pirolisis untuk memproduksi Grafena dipanaskan hingga 600 oC selama satu jam. Grafena yang dihasilkan dikarakterisasi menggunakan XRD, SEM-EDX, TEM, Raman, and Konductometer. Hasil analisis difraktogram sinar-X mengungkapkan bahwa puncak pada 2θ = 24,22o dan 44o tidak terlalu tajam dan sedikit melebar. Ini berarti Grafena terbentuk dengan baik. Analisis SEM-EDX mengungkapkan bahwa ukuran permukaan dan struktur bentuk lebih kecil dan lebih tipis dan itu adalah tumpukan datar yang didominasi oleh atom karbon. Hasil analisis konduktometer menunjukkan konduktivitas listrik Grafena cukup baik, namun Grafena masih belum mampu mengontrol pergerakan elektron. Grafena memiliki jarak lapisan antara lapisan Grafena dan Grafena adalah 3,3 Å (data TEM) dengan jumlah lapisan Grafena adalah 0,85 (multilapisan) (data Raman).